Perkembangan Fisik Peserta Didik Individu di SD IT Al Hijrah 2 Deli Serdang - Rifki Fali; M. Fadhil Ardhiyansyah; Nugraha Aditama Putra Perdana; Loveyanni Marito Benedikta Gorat; M. Fattah; Laili Tanzila; Muhammad Fahri Hafiz; Alfi Rahmadhani; Tirta Yasa Agung Barus; Waliyul Maulana Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
Physical growth is the process of change that occurs in the size, shape and structure of an individual's body as they age. In the context of education, understanding physical growth is very important as it can affect the learning process and overall development of learners. In essence, growth emphasises the physical changes of each child. At this time they need balanced nutrition, so that physical growth can be in accordance with the stages that should be. Growth is expected to be in accordance with the developmental tasks that must be passed. This study uses a survey approach research method which is part of a quantitative approach, with observation, interview, questionnaire filling, and documentation techniques. The research subjects were principals, teachers, parents, and students. The results showed that there are differences in how to educate children in the past era with the current one, and also in accordance with what we read in journals and books that are the reference of this research.